THU0524 IL-1-β and Tnf-α Promote Monocyte Survival and Proliferation through the Induction of GM-CSF Expression by Rheumatoid Arthritis Synovial Fibroblasts. (10th June 2014) - Christelle, D.-L.; Boutet, M.-A.; Chatelais, M.; Brion, R.; Blanchard, F.; Heymann, D.; Le Goff, B.
Abstract : Background: Macrophages and synovial fibroblasts are two major cells implicated in the pathogenesis of rheumatoid arthritis (RA). They can interact in the synovial micro-environment to drive inflammation and bone destruction. It has been hypothesized that synovial fibroblasts were a source of cytokines and growth factors driving macrophages survival and activation. Objectives: The goal of our work was to determine the effects of synovial fibroblasts on monocyte survival and phenotype and to identify which factors were implicated in these effects. Methods: Synovial fibroblasts (SF's) were isolated from synovial tissue of RA patients and CD14+ cells were magnetically isolated from peripheral blood of healthy donors by MACS technology. SF's conditioned media was collected after 24 hours of culture with or without stimulation with TNF-α or IL-1-β. Monocyte survival was assessed using a WST-1 viability assay after 3 days of culture with SF' conditioned media, M-CSF (25 ng/mL) or medium alone. The role of M-CSF, IL-34 and GM-CSF was assessed using specific blocking antibodies. Macrophages polarisation was studied by FACS analysis of the cell surface markers for classical (CD14), non classical (CD16), M1 (CD64), M2a (CD200R) and M2c (CD163) macrophages Real-time RT-PCR was used to study M-CSF, IL-34 and GM-CSF expression by SF's and ELISA assay to measure GM-CSF, M-CSF, IL-34, TNF-α and IL-1-β concentration in the synovial fluid from osteoarthritis (OA) and RA patients. A non-parametric test (Kruskall Wallis) was used to perform statistical analysis. Results: Conditioned media from SF's significantly increased monocytes survival by 60% compared to CD14+ cells cultured in medium alone (p<0.001), with no difference with the survival induced by M-CSF. This effect was enhanced using conditioned media from IL-1-β and TNF-α stimulated SF's with a significant increase in monocyte survival compared to M-CSF (+29% (p=0.05) and +52% (p=0.004) for TNF-α and IL-1-β respectively). M-CSF, GM-CSF and IL-34 mRNA were expressed by SF's and up-regulated after IL-1-β and TNF-α stimulation. Interestingly, IL-1-β was the more potent stimulator of GM-CSF production by SF's both at the mRNA and protein level. M-CSF and IL-34 blocking antibodies had no effect on monocytes survival induced by SF's conditioned media whereas GM-CSF blocking resulted in a significant decrease of monocyte survival by 30% when added to the conditioned media from IL-1-β and TNF-α stimulated SF's (p<0.001). GM-CSF, M-CSF and GM-CSF were all expressed at a higher level in the synovial fluid of RA compared to OA patients with a positive correlation between IL-1-β, TNF-α and GM-CSF concentration. Finally, we did not find any regulation of the cell surface markers of M1 or M2 polarisation on the monocytes differentiated in presence of SF's conditioned media Conclusions: Conditioned media from SF's increased monocyte survival with a greater effect observed with SF's stimulated with IL-1-β and TNF-α. SF's expressed the main monocytes survival factors (M-CSF, IL-34 and GM-CSF) but only a GM-CSF blocking antibody was able to inhibit the SF's conditioned media effect. Targeting GM-CSF could be a good therapeutic option to prevent monocyte survival induced by SF's in the inflamed joint. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4649